The in-out spatial relation as conceptualized and verbalized by Danish Directional Adverbs and their equivalents in Polish - Kacprzak, Aleksander (Folia Scandinavica Posnaniensia, 2019)
The present paper aims to investigate and compare the conceptualization and verbalization of the in-out relation in Danish and Polish. The introductory paragraphs focus on the differences in the distribution of content in Polish and Danish employing Leonard Talmy’s typological classification of languages into verb-framed and satellite-framed, and provide information about Danish Directional Adverbs which are believed to be the key to understanding spatial relations in Danish. The analysis in the following paragraph reveals similarities and differences in the perception of the in-out relation through image schemas such as container and center-periphery. The analysis of the center-periphery image schema in Danish reveals that there is often a presupposed reference point in situations where the directional adverb does not refer to the in-out relation denoted by the prepositional phrase, which leads to a description of the general structure of this image schema in the last part of the article.